Combination of Paclobutrazol Plant Growth Regulator and Organic Fertilizer on Grapevine Growth Quality at a Grape Enthusiast Vineyard, East Jakarta - Eryna Elfasari Rangkuti; Mardiah Laili; Adrianus Putra Pratama Zega (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Global viticulture faces significant agronomic challenges driven by climate change and abiotic stresses, necessitating resilient propagation systems. While synthetic auxins are conventionally used to induce adventitious rooting in stem cuttings, their prolonged application poses ecological and economic detriments. This study aimed to evaluate the synergistic effects of natural botanical biostimulants and stem cutting positions on the early vegetative morphogenesis of grapevine (Vitis vinifera L.) cuttings. A 4x2 factorial Completely Randomized Design (CRD) was conducted in an urban greenhouse, testing four biostimulant treatments (control, onion extract, coconut water, and aloe vera gel) across two stem positions (middle and basal internodes). Vegetative parameters were monitored over five weeks and analyzed using Two-Way ANOVA. The results demonstrated that botanical extracts significantly disrupted bud dormancy and accelerated organogenesis compared to the control. Onion extract exhibited superior performance in stimulating leaf proliferation, yielding an average of 11.5 true leaves—a 300% increase over the control. Conversely, aloe vera extract maximized apical shoot elongation, reaching 9.25 cm. Morphological initiation was highly dependent on the ontogenetic status of the propagation material; middle cuttings consistently outperformed basal cuttings due to an optimal carbon-nitrogen (C/N) ratio and reactive parenchymal tissue. In conclusion, the factorial integration of onion extract with middle stem cuttings provides a highly precise, low-cost eco-propagation strategy.